2016
DOI: 10.1186/s13071-016-1710-3
|View full text |Cite
|
Sign up to set email alerts
|

Humoral and cellular immune responses induced by the urease-derived peptide Jaburetox in the model organism Rhodnius prolixus

Abstract: BackgroundAlthough the entomotoxicity of plant ureases has been reported almost 20 years ago, their insecticidal mechanism of action is still not well understood. Jaburetox is a recombinant peptide derived from one of the isoforms of Canavalia ensiformis (Jack Bean) urease that presents biotechnological interest since it is toxic to insects of different orders. Previous studies of our group using the Chagas disease vector and model insect Rhodnius prolixus showed that the treatment with Jack Bean Urease (JBU) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 77 publications
0
35
0
Order By: Relevance
“…These data is in line with a previous report demonstrating that abdominal injections of JBU did not cause the death of adult cockroaches (Carrazoni et al, 2016). On the contrary, when R. prolixus and T. infestans were tested under similar doses, the triatomines had 100% of mortality after 72 hr or less (Fruttero et al, 2016; Galvani et al, 2015), confirming that they are susceptible to the Jbtx effects and N. cinerea is resistant. Jbtx causes harmful effects and death on several insect species, belonging to the orders Hemiptera ( Oncopeltus fasciatus, Dysdercus peruvianus ), Diptera ( Aedes aegypti ), Lepidoptera ( Spodoptera frugiperda and Helicoverpa armigera ; Becker‐Ritt, Portugal, & Carlini, 2017), and Blattodea ( Blattella germanica ; Carlini & Ligabue‐Braun, 2016).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…These data is in line with a previous report demonstrating that abdominal injections of JBU did not cause the death of adult cockroaches (Carrazoni et al, 2016). On the contrary, when R. prolixus and T. infestans were tested under similar doses, the triatomines had 100% of mortality after 72 hr or less (Fruttero et al, 2016; Galvani et al, 2015), confirming that they are susceptible to the Jbtx effects and N. cinerea is resistant. Jbtx causes harmful effects and death on several insect species, belonging to the orders Hemiptera ( Oncopeltus fasciatus, Dysdercus peruvianus ), Diptera ( Aedes aegypti ), Lepidoptera ( Spodoptera frugiperda and Helicoverpa armigera ; Becker‐Ritt, Portugal, & Carlini, 2017), and Blattodea ( Blattella germanica ; Carlini & Ligabue‐Braun, 2016).…”
Section: Discussionmentioning
confidence: 95%
“…In addition, different reports showed higher resistance of N. cinerea against nematode infection and spider venom when compared to other cockroach species, including B. germanica (Cutler, Hughes, & Rae, 2017; Wullschleger & Nentwig, 2002). In R. prolixus , our group reported that the cellular immune response of hemocyte cellular aggregation is dependent on eicosanoids of the cyclooxygenase pathway (prostaglandins and thromboxanes; Fruttero et al, 2016). Future studies will be directed to elucidate whether this enzymatic pathway is involved in the resistant phenotype of N. cinerea .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides interfering with diuresis, crop physiology and causing effects related to the central nervous system (CNS), JBTX was shown to disrupt the immune response of R. prolixus , affecting the ability of the insect to effectively counteract bacterial infection [24]. …”
Section: What’s New?mentioning
confidence: 99%
“…However, a limited number of studies have focused on the introduction of different foreign substances, such as peptides, into the insect's system with the aim of properly understanding the mechanisms of the immune responses of different insect species. Several related studies, including those of Windley et al (2012) and Fruttero et al (2016), developed novel bioinsecticides, as in the present study. For example, Hardy et al (2013) successfully developed an oral insecticidal toxin, OAIP-1, from the Australian tarantula, Selenotypus plumipes, to combat the agronomically important cotton bollworm, Helicoverpa armigera.…”
Section: Sample Selectionmentioning
confidence: 99%